Management of Complex Facial Lacerations in the Emergency Department - Badeau, Austin (Clin Pract Cases Emerg Med, 2017)
Laceration injuries comprise over 8% of all emergency department (ED) visits annually.1 Given that laceration injuries represent a significant volume of ED visits, emergency physicians (EP) should be comfortable treating these types of injuries. We present the case of a 34-year-old male who presented to the ED as a trauma activation who suffered multiple injuries including complex full-thickness lacerations to his face. While there are scenarios in which consulting a specialist is necessary, knowledge and application of basic wound closure principles allows for many complex lacerations to be repaired by EPs. We provide a helpful systematic approach to evaluating and treating complex facial lacerations in the ED.